Optimalisasi Sarana Prasarana Water Park Tiara Kota Gorontalo - Bambang Suharto; Lisna Bantulu (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2020)
The purpose of this study is to investigate the optimization of water infrastructure and facilities in the city of Gorontalo Tiara boom as well as to determine the condition of water infrastructure boom Tiara Gorontalo. Data analysis techniques used in this study is a qualitative description techniques by processing the data in getting on the field of observation, interviews and documentation. The results of this study, discusses the infrastructure and constraints that exist in water boom Tiara Gorontalo, in particular the benefits of each of the infrastructure that is provided in the water boom Tiara Gorontalo. Because based on my survey results are still a lot of infrastructure that has not been feasible in use that can endanger visitors or tourists, and while that which is feasible in use but have not functioned. Therefore infrastructure water boom Tiara Gorontalo need to be on guard and be noticed again that the safety of visitors or tourists are guaranteed and infrastructures which provide better so that visitors and tourists can feel satisfied and happy after visiting the water boom Tiara Gorontalo.